Characterization of HPMC and PEG 400 Mucoadhesive Film Loaded with Retinyl Palmitate and Ketorolac for Intravaginal Administration - Hernandez Gonzalez, Mariel Eunice; Rodriguez Gonzalez, Claudia; Hernandez Paz, Juan Francisco; Jimenez Vega, Florinda; Olivas Armendariz, Imelda; Valencia Gómez, Laura E; Salcedo, Mauricio (2024)
Intravaginal drug administration offers several advantages over other routes, primarily bypassing the initial stages of metabolism. Additionally, this route has demonstrated both local and systemic effects. Mucoadhesive polymeric systems can be utilized to prevent dose loss due to the mucous barriers and the formation of wet cavities. This study employed various techniques to evaluate the performance and characteristics of a mucoadhesive film composed of HPMC-PEG 400 containing retinyl palmitate and ketorolac molecules. Scanning Electron Microscopy (SEM) was employed to analyze the porous structure of the film. Thermogravimetric Analysis (TGA) was conducted at different temperatures to assess thermal stability. Fourier Transform Infrared Spectroscopy (FTIR) was used to analyze the functional groups and intermolecular interactions between the film and the drug. Swelling and weight loss tests indicated that the film disintegrated within 3–4 days. UV-VIS spectroscopy was used for drug release evaluation based on the Higuchi equation. Additionally, the surface wetting properties were assessed through contact angle measurements. The system’s biocompatibility was confirmed using the MTT assay. Finally, adhesion and glide tests demonstrated the film’s interaction with porcine uterine tissue. This study shows that the HPMC-PEG 400 film containing retinyl palmitate molecules interacts effectively with tissue and could be considered a novel tool for treating damaged epithelial tissues